Dangerously close: The CSB's investigation into the fatal fire and explosion in west, Texas. Issue 4 (10th November 2016) - Banks, Johnnie
Abstract : This article will focus on the fatal explosion and fire which occurred on April 17, 2013, at West Fertilizer in West, Texas, resulting in 15 fatalities, more than 260 injuries, and widespread community damage. The deadly fire and explosion occurred when about 30 tons of fertilizer grade ammonium nitrate exploded after being heated by a fire at the storage and distribution facility. The US Chemical Safety Board deployed an investigative team to examine the incident and conducted a thorough root cause investigation of the massive fire and explosion. © 2016 American Institute of Chemical Engineers Process Saf Prog 35: 312–316, 2016